Xenograft enriched with autologous bone marrow in inlay reconstructions: A tomographic and histomorphometric study in rabbit calvaria - De Oliveira E Silva, Marcelo (2012)
Objective. The aim of this study was to evaluate the bone healing after the usage of a scaffold enriched with bone marrow. Study Design. Ten rabbits were divided into 2 groups of 5 animals. Bilateral 12 mm diameter defects were created in the parietal bones. In control group Bio-Oss were inserted in both defects and, in experimental group, Bio-Oss enriched with autologous bone marrow were inserted in both defects. In these two groups, one of the calvarial defects was covered with Bio-Gide. The rabbits were sacrified 8 weeks after surgery and both CT and histomorphometric analysis were done. Results. The CT showed a lower remaining defect area in the experimental group covered with Bio-Gide when compared with control group, with and without Bio-Gide. The histomorphometrics showed no difference between groups regarding the non-vital mineralized tissue area. For vital mineralized tissue area, the experimental group covered with Bio-Gide obtained a higher percentage area when compared with control group, with and without Bio-Gide. For non-mineralized tissue area, the experimental group covered with Bio-Gide obtained a lower percentage area when compared with control group, with and without Bio-Gide. Conclusion. Both autologous bone marrow and membrane can contribute to the enhancement of bone healing. Copyright © 2012 Marcelo de Oliveira e Silva et al.